Porous film and copper foil substrate

The porous film material formed by reacting polyimidic acid with polyisocyanate, combined with the thermoset ethylene copolymer resin layer, solves the problem of insufficient dielectric performance and heat resistance in high-frequency applications of existing substrate materials, and realizes the multilayering and high-frequency transmission requirements of high-frequency printed circuit boards.

CN119875191APending Publication Date: 2025-04-25IND TECH RES INST
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202311384075.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-10-24
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

Existing substrate resin materials are difficult to meet the high re-soldering heat resistance, through-hole reliability, low transfer loss and ultra-low dielectric characteristics of printed circuit boards in high-frequency applications.

Method used

A porous film formed by reacting polyimidic acid and polyisocyanate is used as the substrate material. By adjusting the monomer ratio and reaction conditions, a porous film with excellent dielectric properties and suitable mechanical characteristics was prepared, and it was sandwiched between copper foils and a thermoset ethylene copolymer resin layer was sandwiched.

Benefits of technology

It realizes substrate materials with excellent dielectric properties, heat resistance and mechanical strength in high-frequency applications, meeting the multilayer and high-frequency transmission needs of printed circuit boards.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004510503580000021
    Figure BDA0004510503580000021
  • Figure BDA0004510503580000031
    Figure BDA0004510503580000031
  • Figure BDA0004510503580000042
    Figure BDA0004510503580000042
Patent Text Reader

Abstract

The present invention discloses a porous membrane and a copper foil substrate, the porous membrane is formed by reacting polyamic acid and polyisocyanate, and the polyamic acid is composed of: 1-20 parts by mole of (a1) a first diamine having a hydroxyl group; 80 to 99 parts by mole of (a2) a second diamine having no hydroxyl groups; the molar ratio of the polyisocyanate to the (b) dianhydride is 0.25: 100 to 20: 100, and the average pore size of the porous membrane is 500 nm to 2000 nm.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a porous membrane mainly composed of polyimide and the monomers used therein and the ratio thereof. Background Art

[0002] For printed circuit boards used in network-related devices such as servers and routers, substrate materials need to be multilayered in addition to high density. Printed circuit boards require substrate materials with high reflow heat resistance and through-hole reliability, as well as low transmission loss.

[0003] With the development of wireless transmission products and high-frequency transmission technology, existing substrate resin materials are difficult to meet advanced applications. For example, when making printed circuit boards, poor wire adhesion is prone to occur after solvent cleaning, and the melting point is close to the glass transition temperature (Tg) and it is difficult to withstand soldering operations above 250°C; or the dielectric properties cannot meet the requirements of ultra-low dielectric (Dk<2.0).

[0004] Therefore, how to develop materials with excellent dielectric properties and meet other characteristics of printed circuit boards, such as high heat resistance, high dimensional stability, high mechanical strength, etc., and apply them to the manufacture of high-frequency printed circuit boards is an urgent problem that printed circuit board material suppliers need to solve at this stage. Summary of the invention

[0005] The porous membrane provided by one embodiment of the present invention is formed by the reaction of polyamic acid and polyisocyanate, and the polyamic acid is formed by the reaction of: 1 to 20 molar parts of (a1) a first diamine having a hydroxyl group; 80 to 99 molar parts of (a2) a second diamine having no hydroxyl group; and 100 molar parts of (b) a dianhydride, wherein the molar ratio of the polyisocyanate to the (b) dianhydride is 0.25:100 to 20:100, and the average pore size of the porous membrane is 500nm to 2000nm.

[0006] A copper foil substrate provided by one embodiment of the present invention comprises: the above-mentioned porous film sandwiched between two copper foils; and two thermosetting ethylene copolymer resin layers sandwiched between the porous film and the copper foils, respectively. DETAILED DESCRIPTION

[0007] The porous membrane provided by one embodiment of the present invention is formed by the reaction of polyamic acid and polyisocyanate, and the polyamic acid is formed by: 1 to 20 molar parts of (a1) a first diamine having a hydroxyl group; 80 to 99 molar parts of (a2) a second diamine having no hydroxyl group; and 100 molar parts of (b) a dianhydride. If the proportion of the first diamine (a1) is too low, the network density and pore skeleton strength that can be formed may be insufficient, and too low pore skeleton strength may result in poor mechanical strength characteristics, limiting the use of the material when subjected to mechanical stress. If the proportion of the first diamine (a1) is too high, it is easy to cause the network density formed to be too large, which increases the rigidity and brittleness of the material and makes it difficult to process.

[0008] For example, if (a1) the first diamine is 2,2-bis(3-amino-4-hydroxyphenyl)hexafluoropropane (6FAP), (a2) the second diamine is a combination of 4,4'-diamino-2,2'-dimethyl-1,1'-biphenyl (DMB) and 4,4'-oxydianiline (ODA), and (b) the dianhydride is a combination of 3,3',4,4'-biphenyltetracarboxylic dianhydride (BPDA) and pyromellitic dianhydride (PMDA), then the structure of the polyamic acid is as follows:

[0009]

[0010] In the above formula, the side chain of the polyamic acid has a hydroxyl group. The polyisocyanate added later will react with the above hydroxyl group to crosslink. The amine group and the carboxyl group of the polymer main chain then undergo a ring-closing reaction to form a polyimide porous membrane. It is understood that the above (a1) first diamine, (a2) second diamine, and (b) dianhydride are only used to illustrate and not to limit the present invention. Other types of (a1) first diamine, (a2) second diamine, and (b) dianhydride also belong to the scope of the present invention.

[0011] In some embodiments, the molar ratio of polyisocyanate to (b) dianhydride is 0.25:100 to 20:100 or 0.5:100 to 20:100. If the proportion of polyisocyanate is too low, the network density formed is insufficient, and it is easy to expand and shrink with temperature changes, resulting in a larger thermal expansion coefficient. If the proportion of polyisocyanate is too high, the network density formed and the proportion of bonds that are easily cracked at high temperatures are too high, which in turn reduces the heat resistance of the material. Excessive network density will increase the hardness and brittleness of the material and reduce the porosity.

[0012] In some embodiments, the average pore size of the porous membrane is 500 nm to 2000 nm. If the average pore size of the porous membrane is too small, it is easy to deform when heated, resulting in pore collapse, and the pore skeleton strength is not enough to resist the influence of surface tension and capillary force during the drying process, and the porous membrane cannot be prepared by normal pressure drying. If the average pore size of the porous membrane is too large, the dielectric constant and dielectric loss factor of the material will increase.

[0013] In some embodiments, the structure of the first diamine (a1) is H 2 N-Ar 1 -NH 2 , where Ar 1 for

[0014] or a combination of the above, where R 1 For-SO 2 -、-C(CH 3 ) 2 -, or -C(CF 3 ) 2 -.

[0015] In some embodiments, the structure of the second diamine (a2) is H 2 N-Ar 2 -NH 2 , where Ar 2 For -(CH 2 ) n -、 or a combination of the above, wherein n=1-10, wherein R 2 -H, -CH 3 , -CF 3 , or -OCH 3 , where R 3 -O-, -S-, -CH 2 -, -CO-, -SO 2 -、-CONH-、-C(CH 3 ) 2 -、-C(CF3 ) 2 -、-O(CH 2 ) 3 O-、-O(CH 2 ) 4 O-, Where R 4 -O-, -CH 2 -, -CO-, -SO 2 -、 And R 5 -O-, -CH 2 -、-CONH-、

[0016] In some embodiments, the structure of (b) dianhydride is Among them, Ar 3 for

[0017]

[0018]

[0019] or a combination of the above, where R 6 For -O-, -S-, -C≡C-, -CO-, -COO-, -SO 2 -、-C(CF 3 ) 2 -、-COO(CH 2 ) 2 OCO-

[0020] In some embodiments, the polyisocyanate is a diisocyanate, a triisocyanate, a tetraisocyanate, or a combination thereof, wherein the diisocyanate has a structure of OCN-R 7- NCO, where R 7 For -(CH 2 ) 5 -、-(CH 2 ) 6 -、 Or a combination of the above; wherein the structure of the triisocyanate is Where R 8 for

[0021]

[0022] The above combination, where R 9 For -(CH 2 ) 6 -, R 10 Each is independently -(CH 2 ) 6 -、 The tetraisocyanate is tetraisocyanate silane, 4,4'-benzylidene bis(6-methyl-m-phenylene) tetraisocyanate, or a combination thereof.

[0023] In some embodiments, the porous membrane has a dielectric constant of <1.4 and a dielectric loss factor of <0.02 at 10 GHz.

[0024] A copper foil substrate provided by one embodiment of the present invention comprises: the above-mentioned porous film sandwiched between two copper foils; and two thermosetting ethylene copolymer resin layers sandwiched between the porous film and the copper foils, respectively.

[0025] In some embodiments, the thermosetting ethylene copolymer resin layer includes a diblock or triblock hydrogenated styrene elastomeric resin or a hydrogenated (styrene-isoprene) copolymer.

[0026] In some embodiments, the copper foil substrate has a dielectric constant of <2.0 and a dielectric loss factor of <0.01 at 10 GHz.

[0027] In order to make the above contents and other purposes, features, and advantages of the present invention more clearly understood, embodiments are given below, which are detailed as follows:

[0028] [Example]

[0029] In the following examples, the density of the porous membrane was measured according to ASTM D792, the average pore size was measured by analyzing the microstructure of the material using a scanning electron microscope, the porosity was measured according to ASTM D6226, and the thermal decomposition temperature (T d 5%) is measured by ASTM E2550, the thermal expansion coefficient is measured by ASTM E831, the compression modulus is measured by ASTM D695-10, the compression strength @10% strain is measured by ASTM D695-10, the dielectric constant and dielectric loss factor at 10 GHz are measured by ASTM D2520, and the volume shrinkage (%) at 300°C for 2 hours is measured by using a digital caliper to measure the length, width, and thickness before and after baking at 300°C to calculate the volume change.

[0030] In the following embodiments, the peel strength test method of the copper foil substrate is ASTM D1876, the solder resistance test method is to immerse the copper foil substrate in a 260°C solder bath for 10 seconds and 30 seconds respectively, observe whether any deformation of the copper foil substrate occurs during the test, and perform visual confirmation to evaluate its solder resistance (refer to Japanese patent JP4912021B2), and the dielectric constant and dielectric loss factor at 10 GHz are measured according to ASTM D2520.

[0031] Example 1 (Preparation of polyamic acid having a hydroxyl reactive functional group in the side chain)

[0032] DMB (0.49 molar parts), ODA (0.49 molar parts), and 6FAP (0.02 molar parts) were added to the reactor and stirred with N-methylpyrrolidone (1-Methyl-2-pyrrolidone, NMP) at room temperature until all monomers were completely dissolved. Then BPDA (0.8 molar parts) and PMDA (0.2 molar parts) were added to the reactor and stirred overnight to obtain a polyamic acid having a hydroxyl reactive functional group in the side chain, with a solid content of about 15wt%, and the solvent was NMP. The structure of the above polyamic acid is as follows:

[0033]

[0034] (Preparation of side chain cross-linked polyimide porous membrane)

[0035] Take the above polyamic acid, polyisocyanate (purchased from Covestro AG) N3300A, 0.013 molar parts), and NMP (500g) were mixed and heated to 80℃~100℃ for 3 hours, and then acetic anhydride (Acetic anhydride, 8 molar parts) and pyridine (Pyridine, 8 molar parts) were added quickly and continuously. The resulting sol was stirred for 5 minutes until fully mixed, and then poured into a mold and left overnight at room temperature. The gel sample was then removed from the mold and the solvent was replaced in sequence with the co-solvent composition (a mixture of NMP and acetone), slowly replacing from 25% acetone to 100% acetone solvent. After the solvent replacement was completed, the gel sample was moved to a sealed pressure vessel, and the pressure vessel was heated to 40℃ while introducing 1200psi CO 2 , regularly and slowly discharge CO 2 The mixture of acetone and supercritical CO is removed until all acetone solvent in the pressure vessel is removed. The pressure vessel is then depressurized until it returns to atmospheric pressure, and the supercritical CO can be taken out. 2 The side chain cross-linked polyimide aerogel substrate (i.e., porous membrane) prepared by drying has a density of 0.17 g / cm 3, porosity is 92.8%, average pore size is 500nm to 2000nm, thermal cracking temperature (T d 5%) is 503°C, the coefficient of thermal expansion is 29ppm / °C, the compression modulus is 22.5MPa, the compressive strength@10% strain is 0.97MPa, the dielectric constant at 10GHz is 1.375 and the dielectric loss factor is 0.0135, and the volume shrinkage (%) at 300°C for 2 hours is 15%.

[0036] Example 2 (Preparation of side chain cross-linked polyimide porous membrane)

[0037] Similar to Example 1, the difference is that after the solvent replacement is completed, the acetone solvent is evaporated at room temperature and air circulation. Then the sample is dried in an oven at 80°C for 2 hours to obtain a side chain cross-linked polyimide aerogel substrate (i.e., a porous membrane) prepared by atmospheric drying. The density of the porous membrane is 0.23 g / cm 3 , porosity is 91.4%, average pore size is 500nm to 2000nm, thermal cracking temperature (T d 5%) is 506°C, the coefficient of thermal expansion is 30ppm / °C, the compression modulus is 19.2MPa, the compressive strength@10% strain is 1.14MPa, the dielectric constant at 10GHz is 1.395 and the dielectric loss factor is 0.0095, and the volume shrinkage (%) at 300°C for 2 hours is 14%.

[0038] Comparative Example 1 (Preparation of a polyamic acid having no hydroxyl reactive functional group in the side chain)

[0039] DMB (0.54 molar parts) and ODA (0.54 molar parts) were added to the reactor and stirred with NMP at room temperature until all monomers were completely dissolved. BPDA (0.8 molar parts) and PMDA (0.2 molar parts) were then added to the reactor and stirred overnight to obtain polyamic acid having no hydroxyl reactive functional groups in the side chains, with a solid content of about 15 wt%, and the solvent was NMP.

[0040] (Preparation of Main Chain End Cross-linked Polyimide Porous Membrane)

[0041] Take the above polyamic acid, N3300A (0.053 molar parts) and NMP (500 g) were mixed, and then acetic anhydride (8 molar parts) and pyridine (8 molar parts) were added quickly and continuously. The resulting sol was stirred for 5 minutes until fully mixed, and then poured into a mold and left overnight at room temperature. The gel sample was then removed from the mold and the co-solvent composition (a mixture of NMP and acetone) was sequentially replaced with solvents, starting from 25% acetone and slowly replaced with 100% acetone solvent. After the solvent replacement was completed, the gel sample was moved to a sealed pressure vessel, and the pressure vessel was heated to 40°C while introducing 1200 psi of CO 2 , regularly and slowly discharge CO 2 The mixture of acetone and supercritical CO is removed until all acetone solvent in the pressure vessel is removed. The pressure vessel is then depressurized until it returns to atmospheric pressure, and the supercritical CO can be taken out. 2 The main chain end cross-linked polyimide aerogel substrate (i.e., porous membrane) prepared by drying has a density of 0.20 g / cm 3 , porosity is 91.9%, average pore size is 50nm to 300nm, thermal cracking temperature (T d 5%) is 500°C, shrinkage deformation occurs and pores collapse when heated, making it impossible to measure the thermal expansion coefficient, the compression modulus is 11.7MPa, the compressive strength @10% strain is 0.76MPa, the dielectric constant at 10GHz is 1.450 and the dielectric loss factor is 0.0164, and the volume shrinkage (%) at 300°C for 2 hours is 90%.

[0042] Comparative Example 2 (Preparation of Main Chain End Cross-linked Polyimide Porous Membrane)

[0043] Similar to Comparative Example 1, the difference is that after the solvent replacement is completed, the acetone solvent is evaporated at room temperature and air circulation. The sample is then dried in an oven at 80°C for 2 hours. When the sample is dried, the pores collapse and the PI porous membrane cannot be prepared. The density of the dried sample is 1.33 g / cm 3 .

[0044] Example 3 (Preparation of polyamic acid having hydroxyl reactive functional groups in the side chain)

[0045] 2,2'-Bis(trifluoromethyl)benzidine (TFMB, 0.7 molar parts), 2,2-bis[4-(4-aminophenoxy)phenyl]propane (BAPP, 0.29 molar parts), and 6FAP (0.01 molar parts) were added to the reactor and stirred with NMP at room temperature until all monomers were completely dissolved. Then, 4,4'-oxydiphthalic anhydride (ODPA, 0.7 mol part) and benzophenone-3,3',4,4'-tetracarboxylic dianhydride (BTDA, 0.3 mol part) were added into the reactor, and after stirring overnight, a polyamic acid having a hydroxyl reactive functional group in the side chain was obtained, the solid content of which was about 15 wt%, and the solvent was NMP.

[0046] (Preparation of side chain cross-linked polyimide porous membrane)

[0047] Take the above polyamic acid, N3300A (0.007 molar parts) is mixed with NMP (500g), heated to 80℃~100℃ for reaction for 3 hours, and then acetic anhydride (Acetic anhydride, 8 molar parts) and pyridine (Pyridine, 8 molar parts) are added quickly and continuously. The resulting sol is stirred for 5 minutes until fully mixed, and then poured into a mold and left overnight at room temperature. The gel sample is then removed from the mold and the solvent is replaced in sequence with the co-solvent composition (a mixture of NMP and acetone), slowly replacing from 25% acetone to 100% acetone solvent. After the solvent replacement is completed, the acetone solvent is evaporated at room temperature with air circulation. The sample is then dried in an oven at 80℃ for 2 hours to obtain a side-chain cross-linked polyimide aerogel substrate (i.e., a porous membrane) prepared by normal pressure drying. The density of the above-mentioned porous membrane is 0.23g / cm 3 , porosity is 91.1%, average pore size is 500nm to 2000nm, thermal cracking temperature (T d 5%) is 510°C, the coefficient of thermal expansion is 37ppm / °C, the compression modulus is 17.6MPa, the compressive strength@10% strain is 1.39MPa, the dielectric constant at 10GHz is 1.354 and the dielectric loss factor is 0.0096, and the volume shrinkage (%) at 300°C for 2 hours is 12%.

[0048] Example 4 (Preparation of polyamic acid having hydroxyl reactive functional groups in the side chain)

[0049] 4,4'-Bis(4-aminophenoxy)biphenyl (BAPB, 0.5 molar parts), p-Phenylenediamine (PPD, 0.4 molar parts), and 6FAP (0.1 molar parts) were added to the reactor and stirred with NMP at room temperature until all monomers were completely dissolved. Then, 4,4'-(Hexafluoroisopropylidene)diphthalic anhydride (6FDA, 0.6 molar parts) and BTDA (0.4 molar parts) were added to the reactor and stirred overnight to obtain a polyamic acid having a hydroxyl reactive functional group on the side chain, with a solid content of about 15wt%, and the solvent was NMP.

[0050] (Preparation of side chain cross-linked polyimide porous membrane)

[0051] Take the above polyamic acid, N3300A (0.067 molar parts) is mixed with NMP (500g), heated to 80℃~100℃ for reaction for 3 hours, and then acetic anhydride (Acetic anhydride, 8 molar parts) and pyridine (Pyridine, 8 molar parts) are added quickly and continuously. The resulting sol is stirred for 5 minutes until fully mixed, and then poured into a mold and left overnight at room temperature. The gel sample is then removed from the mold and the solvent is replaced in sequence with the co-solvent composition (a mixture of NMP and acetone), slowly replacing from 25% acetone to 100% acetone solvent. After the solvent replacement is completed, the acetone solvent is evaporated at room temperature with air circulation. The sample is then dried in an oven at 80℃ for 2 hours to obtain a side-chain cross-linked polyimide aerogel substrate (i.e., a porous membrane) prepared by normal pressure drying. The density of the above-mentioned porous membrane is 0.22g / cm 3 , porosity is 91.8%, average pore size is 500nm to 2000nm, thermal cracking temperature (T d 5%) is 521°C, the coefficient of thermal expansion is 34ppm / °C, the compression modulus is 23.9MPa, the compressive strength@10% strain is 1.22MPa, the dielectric constant at 10GHz is 1.328 and the dielectric loss factor is 0.0101, and the volume shrinkage (%) at 300°C for 2 hours is 6%.

[0052] Example 5 (Preparation of polyamic acid having hydroxyl reactive functional groups in the side chain)

[0053] 9,9'-Bis(4-aminophenyl)fluorene (FDA, 0.5 molar parts), 1,4-Bis(4-aminophenoxy)benzene (TPE-Q, 0.3 molar parts), and 6FAP (0.2 molar parts) were added to the reactor and stirred with NMP at room temperature until all monomers were completely dissolved. Then, 4,4'-(4,4'-isopropylidenediphenoxy)diphthalic anhydride (BPADA, 0.2 molar parts) and BPDA (0.8 molar parts) were added to the reactor and stirred overnight to obtain a polyamic acid having a hydroxyl reactive functional group on the side chain, with a solid content of about 15wt%, and the solvent was NMP.

[0054] (Preparation of side chain cross-linked polyimide porous membrane)

[0055] Take the above polyamic acid, N3300A (0.133 molar parts) is mixed with NMP (500g), heated to 80℃~100℃ for reaction for 3 hours, and then acetic anhydride (Acetic anhydride, 8 molar parts) and pyridine (Pyridine, 8 molar parts) are added quickly and continuously. The resulting sol is stirred for 5 minutes until fully mixed, and then poured into a mold and left overnight at room temperature. The gel sample is then removed from the mold and the solvent is replaced in sequence with the co-solvent composition (a mixture of NMP and acetone), slowly replacing from 25% acetone to 100% acetone solvent. After the solvent replacement is completed, the acetone solvent is evaporated at room temperature with air circulation. The sample is then dried in an oven at 80℃ for 2 hours to obtain a side-chain cross-linked polyimide aerogel substrate (i.e., a porous membrane) prepared by normal pressure drying. The density of the above-mentioned porous membrane is 0.26g / cm 3 , porosity is 90.6%, average pore size is 600nm to 2000nm, thermal cracking temperature (T d 5%) is 518°C, the thermal expansion coefficient is 37ppm / °C, the compression modulus is 28.6MPa, the compressive strength@10% tension is 0.87MPa, the dielectric constant at 10GHz is 1.345 and the dielectric loss factor is 0.0103, and the volume shrinkage (%) at 300°C for 2 hours is 8%.

[0056] Comparative Example 3 (Preparation of polyamic acid having a hydroxyl reactive functional group in the side chain)

[0057] ODA (0.496 mole parts), DMB (0.496 mole parts), and 6FAP (0.008 mole parts) were added to the reactor and stirred with NMP at room temperature until all monomers were completely dissolved. Then BPDA (0.8 mole parts) and PMDA (0.2 mole parts) were added to the reactor and stirred overnight to obtain polyamic acid having hydroxyl reactive functional groups in the side chains, with a solid content of about 15 wt%, and the solvent was NMP.

[0058] (Preparation of side chain cross-linked polyimide porous membrane)

[0059] Take the above polyamic acid, N3300A (0.005 molar parts) is mixed with NMP (500g), heated to 80℃~100℃ for reaction for 3 hours, and then acetic anhydride (Acetic anhydride, 8 molar parts) and pyridine (Pyridine, 8 molar parts) are added quickly and continuously. The resulting sol is stirred for 5 minutes until fully mixed, and then poured into a mold and left overnight at room temperature. The gel sample is then removed from the mold and the solvent is replaced in sequence with the co-solvent composition (a mixture of NMP and acetone), slowly replacing from 25% acetone to 100% acetone solvent. After the solvent replacement is completed, the acetone solvent is evaporated at room temperature with air circulation. The sample is then dried in an oven at 80℃ for 2 hours to obtain a side-chain cross-linked polyimide aerogel substrate (i.e., a porous membrane) prepared by normal pressure drying. The density of the above-mentioned porous membrane is 0.23g / cm 3 , porosity is 91.4%, average pore size is 500nm to 1500nm, thermal cracking temperature (T d 5%) is 509°C, the thermal expansion coefficient is 43ppm / °C, the compression modulus is 12.6MPa, the compression strength@10% tension is 1.07MPa, the dielectric constant at 10GHz is 1.383 and the dielectric loss factor is 0.0099, and the volume shrinkage (%) at 300°C for 2 hours is 13%. It can be seen from Comparative Example 3 that when the amount of 6FAP (i.e., the first diamine (a1)) is too low, the network density and pore skeleton strength formed by the porous membrane are insufficient, and it is easy to expand and shrink with the temperature change, resulting in an increase in the thermal expansion coefficient. Too low pore skeleton strength will also deteriorate the mechanical properties.

[0060] Comparative Example 4 (Preparation of polyamic acid having a hydroxyl reactive functional group in the side chain)

[0061] ODA (0.375 mole parts), DMB (0.375 mole parts), and 6FAP (0.25 mole parts) were added to the reactor and stirred with NMP at room temperature until all monomers were completely dissolved. Then BPDA (0.8 mole parts) and PMDA (0.2 mole parts) were added to the reactor and stirred overnight to obtain polyamic acid having hydroxyl reactive functional groups in the side chains, with a solid content of about 15 wt%, and the solvent was NMP.

[0062] (Preparation of side chain cross-linked polyimide porous membrane)

[0063] Take the above polyamic acid, N3300A (0.167 molar parts) is mixed with NMP (500g), heated to 80℃~100℃ for reaction for 3 hours, and then acetic anhydride (Acetic anhydride, 8 molar parts) and pyridine (Pyridine, 8 molar parts) are added quickly and continuously. The resulting sol is stirred for 5 minutes until fully mixed, and then poured into a mold and left overnight at room temperature. The gel sample is then removed from the mold and the solvent is replaced in sequence with the co-solvent composition (a mixture of NMP and acetone), slowly replacing from 25% acetone to 100% acetone solvent. After the solvent replacement is completed, the acetone solvent is evaporated at room temperature with air circulation. The sample is then dried in an oven at 80℃ for 2 hours to obtain a side-chain cross-linked polyimide aerogel substrate (i.e., a porous membrane) prepared by normal pressure drying. The density of the above-mentioned porous membrane is 0.31g / cm 3 , porosity is 88.7%, average pore size is 600nm to 2700nm, thermal cracking temperature (T d 5%) is 472°C, the thermal expansion coefficient is 33ppm / °C, the compression modulus is 30.8MPa, the compression strength@10% strain is 0.58MPa, the dielectric constant at 10GHz is 1.447 and the dielectric loss factor is 0.0211, and the volume shrinkage (%) at 300° for 2 hours is 10%. It can be seen from Comparative Example 4 that when the amount of 6FAP (i.e., (a1) the first diamine) is too high, the network density ratio formed by the porous membrane is too high, which increases the brittleness of the material and reduces the porosity. In addition, the content of bonds that are easily cracked by high temperature is too high, resulting in a decrease in the heat resistance of the material.

[0064] Example 6

[0065] The selected hydrogenated styrene thermoplastic elastomer SEBS (S1611 purchased from Asahi Chemical Co., Ltd., Japan, 100 g) was dissolved in toluene (500 g), and 0.8 wt % of the initiator diisopropylbenzene peroxide was added.

[0066] (Dicumyl peroxide, DCP) and 2.0wt% of the bridging agent triallylisocyanurate (TAIC) were stirred at 25℃ for 3 hours until they were completely dissolved. The solution with a solid content of 17.8% was coated on the PET release film with a scraper with a gap of 75μm, and dried in an oven at 110℃ for 1 hour to obtain a 15μm thick adhesive layer. The solution with a solid content of 17.8% was coated on the PET release film with a scraper with a gap of 150μm, and dried in an oven at 110℃ for 1 hour to obtain a 30μm thick adhesive layer.

[0067] The mold height of Example 2 was adjusted to prepare porous membranes of about 160 μm, 400 μm, and 730 μm thickness, respectively. An adhesive layer of 15 μm thickness was attached to the upper and lower sides of the porous membrane of about 160 μm thickness, and the three-layer structure was sandwiched between two copper foils of about 12 μm thickness (purchased from Furukawa Chemical), and vacuum pressed at a temperature of 150°C and vacuum reduced pressure to form a copper foil substrate composed of a multilayer film, and its composite structure from top to bottom is copper foil, adhesive layer, porous membrane, adhesive layer, and copper foil. The above copper foil substrate passed the peel strength test and the solder resistance test (260°C solder bath for 10 seconds and 30 seconds), and then the strength was 16.9 N / cm, the dielectric constant at 10 GHz was 1.650, and the dielectric loss factor was 0.0063.

[0068] A 30μm thick adhesive layer is attached to the upper and lower sides of a 400μm thick porous film, and then the three-layer structure is sandwiched between two 12μm thick copper foils (purchased from Furukawa Chemical), and vacuum pressed at a temperature of 150°C and vacuum reduced pressure to form a copper foil substrate composed of a multi-layer film. The composite structure is copper foil, adhesive layer, porous film, adhesive layer, and copper foil from top to bottom. The above copper foil substrate passed the peel strength test and solder resistance test (260°C solder bath for 10 seconds and 30 seconds), and then the strength was 17.7N / cm, the dielectric constant at 10GHz was 1.517, and the dielectric loss factor was 0.0049.

[0069] A 30μm thick adhesive layer was attached to the upper and lower sides of a porous membrane of about 730μm thickness, and the three-layer structure was sandwiched between two copper foils of about 12μm thickness (purchased from Furukawa Chemical), and vacuum pressed at a temperature of 150°C and vacuum reduced pressure to form a copper foil substrate composed of a multi-layer film. The composite structure is copper foil, adhesive layer, porous membrane, adhesive layer, and copper foil from top to bottom. The above copper foil substrate passed the peel strength test and solder resistance test (260°C solder bath for 10 seconds and 30 seconds), and then the strength was 16.3N / cm, the dielectric constant at 10GHz was 1.516, and the dielectric loss factor was 0.0047.

[0070] Comparative Example 5

[0071] The adhesive layer of 30 μm thick in Example 6 was attached to the upper and lower sides of a polyethylene woven cloth of 220 μm thick (CLAF purchased from ENEOStechno materials Corporation), and the three-layer structure was sandwiched between two copper foils of about 12 μm thick (purchased from Furukawa Chemical), and vacuum pressed at a temperature of 150°C and vacuum reduced pressure to form a copper foil substrate composed of a multi-layer film, and its composite structure from top to bottom is copper foil, adhesive layer, polyethylene woven cloth, adhesive layer, and copper foil. The above copper foil substrate passed the peel strength test, and then the strength was 13.5 N / cm, the dielectric constant at 10 GHz was 1.656 and the dielectric loss factor was 0.0008, but failed to pass the solder resistance test (260°C solder bath for 10 seconds and 30 seconds). The above copper foil substrate cannot withstand common processes such as soldering for printed circuit boards, and melts and loses dielectric properties due to the soldering process.

[0072] Although the present invention has been disclosed as above with several embodiments, they are not intended to limit the present invention. Anyone with common knowledge in the technical field can make any changes and modifications without departing from the spirit and scope of the present invention. Therefore, the scope of protection of the present invention shall be based on the scope defined by the attached claims.

Claims

1. A porous membrane is formed by the reaction of polyamic acid and polyisocyanate, wherein the polyamic acid is: 1 to 20 parts by mole of (a1) a first diamine having a hydroxyl group; 80 to 99 parts by mole of (a2) a second diamine having no hydroxyl group; and 100 mol parts of (b) dianhydride are reacted, wherein the molar ratio of polyisocyanate to (b) dianhydride is 0.25:100 to 20:100, The average pore size of the porous membrane is 500nm to 2000nm.

2. The porous membrane according to claim 1, wherein the structure of the first diamine (a1) is H2N-Ar 1 -NH2, of which Ar 1 for or a combination of the above, where R 1 It is -SO2-, -C(CH3)2-, or -C(CF3)2-.

3. The porous membrane according to claim 1, wherein the structure of the second diamine (a2) is H2N-Ar 2 -NH2, of which Ar 2 -(CH2) n -、 or a combination of the above, Where n = 1-10, Where R 2 is -H, -CH3, -CF3, or -OCH3, Where R 3 is -O-, -S-, -CH2-, -CO-, -SO2-, -CONH-, -C(CH3)2-, -C(CF3)2-, -O(CH2)3O-, -O(CH2)4O-, Where R 4 -O-, -CH2-, -CO-, -SO2-, as well as Where R 5 -O-, -CH2-, -CONH-, 4. The porous membrane according to claim 1, wherein the structure of (b) dianhydride is Among them, Ar 3 for or a combination of the above, Where R 6 For -O-, -S-, -C≡C-, -CO-, -COO-, -SO2-, -C(CF3)2-, -COO(CH2)2OCO-, 5. The porous membrane according to claim 1, wherein the polyisocyanate is diisocyanate, triisocyanate, tetraisocyanate, or a combination thereof, The structure of diisocyanate is OCN-R 7 -NCO, where R 7 -(CH2)5-, -(CH2)6-, or a combination of the above; The structure of triisocyanate is Where R 8 for or a combination of the above, Where R 9 is -(CH2)6-, R 10 Each is independently -(CH2)6-, The tetraisocyanate is tetraisocyanate silane, 4,4'-benzylidene bis(6-methyl-m-phenylene) tetraisocyanate, or a combination thereof. The porous membrane according to claim 1 , having a dielectric constant of less than 1.4 and a dielectric loss factor of less than 0.02 at 10 GHz.

7. A copper foil substrate, comprising: The porous membrane of claim 1, sandwiched between two copper foils; Two thermosetting ethylene copolymer resin layers are respectively sandwiched between the porous membrane and the copper foils. 8 . The copper foil substrate according to claim 7 , wherein the thermosetting ethylene copolymer resin layers comprise diblock or triblock hydrogenated styrene elastomer resin.

9. The copper foil substrate according to claim 7, wherein the thermosetting ethylene copolymer resin layers comprise diblock or triblock hydrogenated (styrene-isoprene) copolymers. 10 . The copper foil substrate according to claim 7 , wherein the dielectric constant thereof at 10 GHz is less than 2.0 and the dielectric loss factor thereof is less than 0.01.

Citation Information

Patent Citations

  • Method for producing thermoplastic polyimide resin foam

    JP4912021B2